Pendampingan Psiko-Spiritual Melalui Gerakan Kub Peduli Ibu Hamil untuk Penguatan Kesehatan Mental dan Spiritual Ibu - Damianus Dionisius Nuwa; Maria Yulita C. Age; Grasela Novita Bebe; Maria Helena Enga (Forum Kerjasama Pendidikan Tinggi, 2026)
Pregnant women in the Kevikepan Ende region face various challenges, including limited access to health facilities, long geographical distances, and a lack of psychological and spiritual support during pregnancy. These conditions may increase anxiety and emotional vulnerability, particularly within church-based community settings. In response to this situation, a community service program was implemented through the Basic Ecclesial Community (KUB) Care for Pregnant Women Movement as a form of community-based psycho-spiritual accompaniment. This community service activity aims to provide holistic accompaniment for pregnant women through the active involvement of Basic Ecclesial Communities and parish pastoral services. The accompaniment was carried out through pastoral visits, communal prayers, blessings, solidarity-based support, and the facilitation of routine health check-ups in collaboration with local medical personnel. The implementation methods included direct community accompaniment, participatory observation, and interviews with pregnant women, KUB coordinators, and parish priests as part of activity reflection and evaluation. The results indicate that the KUB Care for Pregnant Women Movement successfully created a safe and inclusive space for pregnant women, reduced anxiety levels, and enhanced psycho-spiritual well-being as well as a sense of meaning and belonging within the community. However, the implementation has not been evenly distributed across all KUB units, highlighting the need for strengthened organizational structures, sustained pastoral accompaniment, and increased capacity-building for KUB members. This community service activity affirms that community-based psycho-spiritual accompaniment represents a contextual, participatory, and relevant pastoral service model for supporting vulnerable groups, particularly pregnant women, and should be integrated into diocesan pastoral policies to ensure program sustainability and broader impact.